Lanthanum-modified fly ash-based ceramsite for treating virus-containing wastewater and preparation method thereof
Through the preparation of lanthanum modified fly ash-based ceramic granules, the problem of poor virus removal effect in sewage was solved, and efficient, stable and low-cost virus removal effect was achieved, with wide application prospects.
Patent Information
- Application Number
- CN202410648084.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-23
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-05-23
AI Technical Summary
The existing sewage treatment process cannot effectively remove the virus, resulting in the virus still exists in the effluent, which poses health risks and high costs.
Using lanthanum modified fly ash-based ceramic granules, it can be prepared by calcining fly ash, clay and lanthanum salt under high temperature aerobic conditions to form ceramic granules with high specific surface area and pore structure, which can effectively remove wastewater. virus.
It has achieved efficient removal of viruses in wastewater, with good stability, low cost, suitable for large-scale applications, and has practical application value.
Smart Images

Figure CN118561584B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite material preparation, and specifically relates to a lanthanum-modified fly ash-based ceramsite for treating virus-containing wastewater and a preparation method thereof. Background Art
[0002] Sewage recycling needs to pay attention to its potential health risks, especially pathogenic microorganisms that are prone to cause diseases. Drinking water microbial contamination caused by fecal contamination is the biggest threat to drinking water safety. Viruses are small (18-1500nm), more resistant to conventional disinfection processes, and have a smaller infection dose (<10-10 3 The current conventional treatment process of sewage treatment plants cannot meet the needs of virus removal. Studies have shown that the primary treatment process, including screens and grit chambers, can remove less than 75% of the virus due to its short hydraulic retention time; the secondary treatment unit of the sewage treatment plant mainly uses traditional biological treatment, which can remove 1-1.5 log of the virus. 10 , but it is greatly affected by the type of virus, and viruses are still detected in the effluent. Since viruses can exist in the environment for a long time, the subsequent sludge disposal process increases the risk of virus transmission. The currently commonly used deep treatment processes such as ultrafiltration, ultraviolet disinfection, ozone disinfection and chlorine disinfection have shortcomings such as high cost and great influence by water quality, and may also produce additional disinfection by-products.
[0003] Fly ash is an industrial solid waste produced by coal combustion. Currently, fly ash is usually used in metal recovery, building materials, soil remediation and wastewater treatment. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a lanthanum-modified fly ash-based ceramsite for treating virus-containing wastewater and a preparation method thereof, so as to solve the technical problem that the virus removal effect in sewage is not good enough.
[0005] To achieve the above object, the technical solution adopted by the present invention is: to provide a method for preparing lanthanum-modified fly ash-based ceramsite for treating virus-containing wastewater, comprising the following steps:
[0006] S1, fly ash and clay are mixed evenly in a mass ratio of 1-3:1, and then 10-30wt% of eggshell powder is added to obtain a matrix powder;
[0007] S2, adding a lanthanum salt solution to the matrix powder, and then mixing evenly to obtain a semi-solid mixture, wherein the content of lanthanum in the semi-solid mixture is 1-3wt%; and then drying to obtain an intermediate ceramsite;
[0008] S3. The intermediate ceramsite is calcined at 900-1050° C. for 5-30 min under aerobic conditions, then cooled to room temperature, washed, and dried to obtain lanthanum-modified fly ash-based ceramsite.
[0009] The main components of fly ash and clay are Si and Al, and the modifier is lanthanum chloride. After the three are mixed, they react under high temperature and aerobic conditions. The silicon aluminum oxide formed by fly ash and clay serves as the base of ceramsite. The main component of eggshell is CaCO3. Through high temperature calcination, the eggshell decomposes to produce carbon dioxide, which generates a porous structure on the surface of the ceramsite, increasing the specific surface area of the ceramsite. At the same time, La is loaded onto its surface in various forms, so that the ceramsite has both the ability to remove viruses and the potential for application.
[0010] On the basis of the above technical solution, the present invention can also be improved as follows:
[0011] Furthermore, the particle size of the lanthanum modified fly ash-based ceramsite is 10-15.5 mm.
[0012] Furthermore, the lanthanum salt is lanthanum chloride.
[0013] Furthermore, the content of lanthanum in the lanthanum salt is 1-3 wt%.
[0014] Furthermore, in steps S2 and S3, the drying temperature is 100-110° C., and the drying time is 80-100 min.
[0015] Furthermore, the calcination temperature is 1000° C. and the calcination time is 20 min.
[0016] Furthermore, the heating rate during calcination is 8-12°C / min.
[0017] The invention also discloses lanthanum-modified fly ash-based ceramsite prepared by the preparation method of lanthanum-modified fly ash-based ceramsite for treating virus-containing wastewater.
[0018] The invention also discloses the application of lanthanum modified fly ash-based ceramsite in treating virus-containing sewage.
[0019] Furthermore, the virus is PhiX174 bacteriophage.
[0020] The beneficial effects of the present invention are:
[0021] 1. The present invention uses industrial solid waste fly ash as the main raw material, and modifies it with lanthanum salt to obtain lanthanum-modified fly ash-based ceramsite. Compared with other virus inactivation materials such as nano zero-valent iron, the lanthanum-modified fly ash-based ceramsite prepared by the present invention has better stability, can remove viruses in wastewater in a long-term and stable manner, and has a controllable particle size and lower cost, which is conducive to large-scale removal of viruses in wastewater and has practical application value.
[0022] 2. The present invention uses industrial solid waste for sewage treatment after treatment to achieve the purpose of "treating waste with waste", which has good economic and environmental benefits and application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a comparison chart of the removal effects of lanthanum-modified fly ash-based ceramsite, unmodified fly ash-based ceramsite and La2O3 on PhiX174;
[0024] Figure 2 This is a comparison chart of the removal effects of lanthanum-modified fly ash-based ceramsite and unmodified fly ash-based ceramsite on PhiX174;
[0025] Figure 3 The scanning electron microscope images of lanthanum-modified fly ash-based ceramsite; Figure (a) is a scanning electron microscope image of the modified ceramsite at 5 μm, Figure (b) is a scanning electron microscope image of the modified ceramsite at 500 nm, Figure (c) is a lanthanum element mapping image, Figure (d) is an oxygen element mapping image, Figure (e) is a silicon element mapping image, and Figure (f) is an aluminum element mapping image;
[0026] Figure 4 is the X-ray diffraction pattern of lanthanum-modified fly ash-based ceramsite;
[0027] Figure 5 This is a comparison chart of the removal effect of PhiX174 on fly ash-based ceramsite modified with different eggshell addition amounts;
[0028] Figure 6 This is a comparison chart of the effect of calcination temperature on the removal of PhiX174;
[0029] Figure 7 This is a comparison chart of the effect of calcination time on the removal of PhiX174;
[0030] Figure 8 The effect of the addition amount of lanthanum-modified fly ash-based ceramsite on the removal efficiency of PhiX174;
[0031] Fig. 9 is the effect of PhiX174 concentration on the removal effect;
[0032] Fig.10 The effect of pH on the removal of PhiX174. DETAILED DESCRIPTION
[0033] The specific embodiments of the present invention are described below to facilitate the understanding of the present invention by those skilled in the art. If the specific conditions are not specified in the examples, the methods are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturers are not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially. However, it should be clear that the present invention is not limited to the scope of the specific embodiments. For those skilled in the art, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations using the concept of the present invention are protected.
[0034] Example 1
[0035] A method for preparing lanthanum-modified fly ash-based ceramsite for treating virus-containing wastewater comprises the following steps:
[0036] S1, 30g of fly ash and 10g of clay were mixed evenly, and then 17.14g of eggshell powder (30wt%) was added to obtain a matrix powder;
[0037] S2, adding 10 mL of 0.107 g / mL lanthanum chloride heptahydrate solution (lanthanum element 1 wt%) to 40 g of the matrix powder, and then mixing to obtain a semi-solid mixture; then forming the semi-solid mixture into spheres with a particle size of 12 mm, and drying the spheres at 105° C. for 30 min to obtain intermediate ceramsite;
[0038] S3. Under aerobic conditions, the temperature is raised from room temperature to 1000°C at a heating rate of 10°C / min, and the intermediate ceramsite is calcined at this temperature for 20 minutes, then cooled to room temperature, washed with water, and finally dried at 105°C for 30 minutes to obtain lanthanum-modified fly ash-based ceramsite.
[0039] Example 2
[0040] A method for preparing lanthanum-modified fly ash-based ceramsite for treating virus-containing wastewater comprises the following steps:
[0041] S1, 40g of fly ash and 20g of clay were mixed evenly, and then 15g of eggshell powder (20wt%) was added to obtain a matrix powder;
[0042] S2, adding 10 mL of 0.214 g / mL lanthanum chloride heptahydrate solution (2 wt% of lanthanum element) to 40 g of the matrix powder, and then mixing evenly to obtain a semi-solid mixture; then forming the semi-solid mixture into spheres with a particle size of 10 mm, and drying the spheres at 100° C. for 40 min to obtain intermediate ceramsite;
[0043] S3. Under aerobic conditions, the temperature is raised from room temperature to 900°C at a heating rate of 8°C / min, and the intermediate ceramsite is calcined at this temperature for 30 minutes, then cooled to room temperature, washed with water, and finally dried at 100°C for 40 minutes to obtain lanthanum-modified fly ash-based ceramsite.
[0044] Example 3
[0045] A method for preparing lanthanum-modified fly ash-based ceramsite for treating virus-containing wastewater comprises the following steps:
[0046] S1, 20g of fly ash and 20g of clay were mixed evenly, and then 4.44g of eggshell powder (10wt%) was added to obtain a matrix powder;
[0047] S2, adding 10 mL of 0.321 g / mL lanthanum chloride heptahydrate solution (3 wt% of lanthanum element) to 40 g of the matrix powder, and then mixing to obtain a semi-solid mixture; then forming the semi-solid mixture into spheres with a particle size of 15.5 mm, and drying the spheres at 110° C. for 20 min to obtain intermediate ceramsite;
[0048] S3. Under aerobic conditions, the temperature is raised from room temperature to 1050°C at a heating rate of 12°C / min, and the intermediate ceramsite is calcined at this temperature for 5 minutes, then cooled to room temperature, washed with water, and finally dried at 110°C for 20 minutes to obtain lanthanum-modified fly ash-based ceramsite.
[0049] Comparative Example
[0050] A method for preparing fly ash-based ceramsite comprises the following steps:
[0051] S1, 30g of fly ash and 10g of clay were mixed evenly, and then 17.14g of eggshell powder (30wt%) was added to obtain a matrix powder;
[0052] S2, the matrix powder is made into a sphere with a particle size of 12 mm, and the sphere is dried at 105° C. for 30 min to obtain an intermediate ceramsite;
[0053] S3. Under aerobic conditions, the temperature is raised from room temperature to 1000°C at a heating rate of 10°C / min, and the intermediate ceramsite is calcined at this temperature for 20 minutes, then cooled to room temperature, washed with water, and finally dried at 105°C for 30 minutes to obtain lanthanum-modified fly ash-based ceramsite.
[0054] In the following examples, PhiX174 is selected as a model for studying virus removal. PhiX174 is a single-stranded DNA, non-enveloped, spherical bacteriophage with a size (26 nm) and structure similar to enterovirus. Its host cell is Escherichia coli and it is non-pathogenic to humans.
[0055] Experimental Example 1 Virus Removal Effect Comparison
[0056] 1. In order to show the role of La in the removal of viruses by modified ceramsite, the lanthanum-modified fly ash-based ceramsite prepared in Example 1 and the unmodified fly ash-based ceramsite prepared in the comparative example were used as ceramsite samples for comparison in this experiment. At the same time, La2O3 was used as the control group to explore its role.
[0057] Weigh 8 g of each of the two ceramsite samples and 0.0938 g of La2O3 (consistent with the mass of La in the lanthanum-modified fly ash-based ceramsite of Example 1) and add them to a 50 mL flask containing 10% PhiX174. 5 PFU / mL in a 100mL conical flask, placed in a constant temperature water bath shaker, and perform PhiX174 removal experiments at 25°C and 150rpm. Samples were taken every 3 hours, and after the sample solution was diluted to an appropriate concentration, PhiX174 was counted using the double-layer agar plate method to calculate the logarithmic removal rate LRV:
[0058]
[0059] Among them, C t is the concentration of PhiX174 in the sample solution after t hours, PFU / mL; C0 is the initial concentration of PhiX174 in the sample solution, PFU / mL.
[0060] The results are as follows Figure 1 As shown in the figure, it can be seen that lanthanum-modified fly ash-based ceramsite has a faster removal rate for PhiX174 than unmodified fly ash-based ceramsite and La2O3, but the removal effect of La2O3 is better than that of unmodified ceramsite. This shows that the way lanthanum-modified fly ash-based ceramsite inactivates viruses is different from that of ordinary lanthanum oxide, and there may be differences in the mechanism of action and the existence form of La.
[0061] 2. In order to further study the removal ability of lanthanum-modified fly ash-based expanded clay on PhiX174, under the same experimental conditions, the reaction time was extended, and samples were taken every 12 hours. After the samples were diluted to an appropriate concentration, the double-layer agar plate method was used to count PhiX174 and the logarithmic removal rate was calculated.
[0062] The results are as follows Figure 2 As shown in the figure, it can be seen that the removal amount of PhiX174 by lanthanum-modified fly ash-based ceramsite is significantly higher than that of unmodified fly ash-based ceramsite, and the removal effect in 12 hours is greater than 3-log 10 (99.9%).
[0063] Experimental Example 2 Elemental Analysis and SEM Analysis
[0064] The surface morphology of the lanthanum-modified fly ash-based ceramsite prepared in Example 1 was characterized by electron microscopy scanning and XRD.
[0065] According to the electron microscope scanning image ( Figure 3 ) shows that the surface of La-modified fly ash-based ceramsite presents a granular porous structure (Figure (a) and Figure (b)), the main components of ceramsite Al and Si form a base Al and Si evenly distributed, the surface is relatively smooth (Figure (a), Figure (e) and Figure (f)), and La is loaded on its surface, forming more rough defects (Figure (a)-Figure (c)), which is conducive to virus inactivation. The ceramsite base ensures the strength of the material, and at the same time, La is successfully loaded on the porous ceramsite surface.
[0066] The composition and structure of the modified ceramsite were measured by X-ray fluorescence spectrometer (XRF) and X-ray diffractometer (XRD). The measurement data are shown in Table 1.
[0067] Table 1 Main components and contents of lanthanum modified fly ash-based ceramsite
[0068]
[0069]
[0070] The XRF results of the modified ceramsite are shown in Table 1 (the table shows components with a content of >1%), and the main components are SiO2, Al2O3 and La2O3, indicating that La is successfully loaded on the ceramsite.
[0071] XRD results are as follows Figure 4 As shown, the main components of ceramsite are Si and Al, which exist mainly in the form of SiO2 (PDF#79-1906) and Al (Al1.272Si0.728O4.864) (PDF#83-1881); at the same time, La reacts during calcination at high temperature and exists mainly in the form of La2O3 (PDF#05-0602) and La2O2C2 (PDF#70-0231). The XRD characterization results confirm the speculation in Experimental Example 1 that the existence form of La in lanthanum-modified fly ash-based ceramsite is different from that of La2O3.
[0072] According to the above characterization results, La-modified fly ash-based ceramsite has the advantages of controllable particle size and strength of ceramsite. At the same time, La is loaded on its surface in various forms, which makes the ceramsite have both the ability to remove viruses and the potential for application.
[0073] Experimental Example 3 Parameter Optimization
[0074] 1. Eggshell addition amount
[0075] Based on the sum of the mass of fly ash and clay, the amount of eggshell added was set to 0wt%, 10wt%, 20wt% and 30wt%, respectively. The remaining components and preparation method were the same as in Example 1 to obtain lanthanum-modified fly ash-based ceramsite A1-A4 groups.
[0076] 2. Calcination temperature
[0077] The calcination temperatures were set to 900° C., 950° C., 1000° C. and 1050° C., respectively. The remaining components and preparation methods were the same as in Example 1, and lanthanum-modified fly ash-based ceramsite groups B1-B4 were obtained.
[0078] 3. Calcination time
[0079] The calcination time was set to 5 min, 10 min, 20 min and 30 min respectively, and the remaining components and preparation method were the same as in Example 1 to obtain lanthanum modified fly ash-based ceramsite C1-C4 groups.
[0080] 8 g of lanthanum-modified fly ash-based ceramsite from groups A1-A4, B1-B4, and C1-C4 were weighed and added to 50 mL of PhiX174 at an initial concentration of 10 5 PFU / mL in a 100mL conical flask, placed in a constant temperature water bath shaker, and perform the PhiX174 removal experiment at 25°C and 150rpm. Samples were taken once after 24 hours of reaction. After the sample solution was diluted to an appropriate concentration, PhiX174 was counted using the double-layer agar plate method to calculate the logarithmic removal rate.
[0081] The results showed that the most influential factor was the amount of eggshell added, followed by calcination temperature and time. All materials passed the strength test and it was found that the amount of eggshell added should not be too large, otherwise it would affect the granulation and expanded clay strength.
[0082] like Figure 5 As shown, 10%-30% was selected as the response surface experiment range;
[0083] like Figure 6 As shown in the figure, the maximum removal is achieved at 1000℃ calcination temperature, and 950℃-1050℃ is selected for response surface experiment.
[0084] like Figure 7 As shown, the best removal effect was achieved when the calcination time was 20 min, and the range selected in the response surface experiment was 10-30 min.
[0085] The response surface design was performed using the Box-Behnken method of Design-Expert 13 software. The factors were: eggshell addition amount-A, calcination temperature-B and calcination time-C. Three levels were set, and the center point was set to 3. There were 15 groups of experiments in total. The regression equation for the logarithmic removal rate (LRV) of PhiX174 was obtained as follows:
[0086] LR V=3.42-0.0032A+0.0589B-0.0491C+0.0412AB-0.0571AC+0.0772BC
[0087] +0.1502A 2 -0.0277B 2 -0.056C 2
[0088] Within the experimental range, the model was significant (P = 0.0174 < 0.05), and the response surface obtained that the preparation conditions of lanthanum-modified fly ash-based ceramsite were 30wt% eggshell addition, calcination temperature of 1000℃, and calcination time of 20min. Under these conditions, three groups of identical modified fly ash-based ceramsite were prepared for PhiX174 removal. The results are shown in Table 2. After 24h of reaction, the logarithmic removal rates were 4.04-log 10 ,4.28-log 10 and 4.09-log 10 , the recurrence rate is high, indicating that the condition is stable and feasible.
[0089] Table 2 Removal effect of optimized modified ceramsite on PhiX174
[0090] Group 1 Group 2 Group 3 Initial concentration (PFU / mL) <![CDATA[2.60×10 6 ]]> <![CDATA[2.60×10 6 ]]> <![CDATA[2.60×10 6 ]]> Concentration after 24h (PFU / mL) 237 136 211 Logarithmic removal rate <![CDATA[4.04-log 10 ]]> <![CDATA[4.28-log 10 ]]> <![CDATA[4.09-log 10 ]]>
[0091] Experimental Example 4 Effect of adding different amounts of modified ceramsite on virus removal
[0092] In order to study the effect of filler dosage on virus removal, the lanthanum-modified fly ash-based ceramsite prepared in Example 1 was used for the experiment. 4 g, 8 g and 12 g of lanthanum-modified fly ash-based ceramsite were weighed and added to 50 mL of PhiX174 with an initial concentration of 10 5 The PhiX174 removal experiment was carried out at a reaction condition of 25°C and 150 rpm in a 100 mL conical flask with a concentration of PFU / mL. Samples were taken every 3 h, and after the sample solution was diluted to an appropriate concentration, PhiX174 was counted using the double-layer agar plate method, and the logarithmic removal rate was calculated.
[0093] The results are as follows Figure 8 As shown in the figure, it can be seen that increasing the amount of modified ceramsite can enhance the removal effect of PhiX174.
[0094] Experimental Example 5 Effect of different initial concentrations of PhiX174 on virus removal
[0095] Weigh 8 g of the lanthanum-modified fly ash-based ceramsite prepared in Example 1 and add them to 50 mL of PhiX174 with an initial concentration of 10 4- 10 8 The PhiX174 removal experiment was carried out at a reaction condition of 25°C and 150 rpm in a 100 mL conical flask with a concentration of PFU / mL. Samples were taken every 12 h, and after the sample solution was diluted to an appropriate concentration, PhiX174 was counted using the double-layer agar plate method to calculate the logarithmic removal rate.
[0096] like Fig. 9 The results showed that when the phage concentration was 6.3×10 4-6 PFU / mL, increasing the initial concentration can improve the reaction rate and removal effect; when the phage concentration is 6.3×10 7-8 PFU / mL, when the concentration is increased, the removal rate and effect will decrease instead. The removal effect can be improved by increasing the amount of material used.
[0097] Experimental Example 6 Effect of different pH values on virus removal
[0098] Weigh 8 g of the lanthanum-modified fly ash-based ceramsite prepared in Example 1 and add them to 50 mL of PhiX174 with an initial concentration of 10 6 The pH value of the mixed solution was set to 5, 6, 7, 8, and 9 respectively in a 100-mL conical flask with 100 PFU / mL, and then placed in a constant temperature water bath shaker. The PhiX174 removal experiment was carried out at 25°C and 150 rpm. Samples were taken every 12 hours, and after the sample solution was diluted to an appropriate concentration, PhiX174 was counted using the double-layer agar plate method to calculate the logarithmic removal rate.
[0099] The results are as follows Fig.10 As shown in the figure, it can be seen that when pH = 6, the removal effect is average, because the pH value of the mixed solution is close to the isoelectric point of PhiX174 6.4. Under other conditions, 4-log 10 about.
Claims
1. A method for preparing lanthanum-modified fly ash-based ceramsite for treating virus-containing wastewater, characterized in that: The following steps are involved: S1, fly ash and clay are mixed evenly in a mass ratio of 1-3:1, and then 10-30wt% of eggshell powder is added to obtain a matrix powder; S2, adding a lanthanum salt solution to the matrix powder, and then mixing evenly to obtain a semi-solid mixture, wherein the content of lanthanum in the semi-solid mixture is 1-3wt%; and then drying to obtain an intermediate ceramsite; S3. The intermediate ceramsite is calcined at 900-1050° C. for 5-30 min under aerobic conditions, then cooled to room temperature, washed, and dried to obtain lanthanum-modified fly ash-based ceramsite; the lanthanum-modified fly ash-based ceramsite exists in the form of La2O3 and La2O2C2.
2. The method for preparing lanthanum-modified fly ash-based ceramsite for treating virus-containing wastewater according to claim 1, characterized in that: The particle size of the lanthanum modified fly ash-based ceramsite is 10-15.5 mm.
3. The method for preparing lanthanum-modified fly ash-based ceramsite for treating virus-containing wastewater according to claim 1, characterized in that: The lanthanum salt is lanthanum chloride.
4. The method for preparing lanthanum-modified fly ash-based ceramsite for treating virus-containing wastewater according to claim 1, characterized in that: The drying temperature in steps S2 and S3 is 100-110° C., and the drying time is 80-100 min.
5. The method for preparing lanthanum-modified fly ash-based ceramsite for treating virus-containing wastewater according to claim 1, characterized in that: The calcination temperature is 1000° C. and the calcination time is 20 min.
6. The method for preparing lanthanum-modified fly ash-based ceramsite for treating virus-containing wastewater according to claim 1 or 5, characterized in that: The heating rate during the calcination is 8-12°C / min.
7. Lanthanum-modified fly ash-based ceramsite prepared by the method for preparing lanthanum-modified fly ash-based ceramsite for treating virus-containing wastewater according to any one of claims 1 to 6.
8. Use of the lanthanum-modified fly ash-based ceramsite according to claim 7 in treating virus-containing wastewater.
Citation Information
Patent Citations
Modified pulverized-fuel-ash ceramic as well as preparation method and application thereof
CN108383540A
High-strength porous environment-protecting filtering haydite with adsorbing film and its making process
CN1548213A